Thanks for Organizing the Conference on the Occasion of My Jubilee - Vuković, Mirjana (Sarajevo Journal of Mathematics, 2024)
My dear colleagues and friends, as well as my ex-students ! It has been such an honour to be a part of the beautiful Conference dedicated to me and my jubilee, that moved me to tears. I would like to extend my heartfelt gratitude to all of you for this wonderful Conference, to all who presented and dedicated your papers to me. I am especially thankful to two of my exceptional ex-students now university professors Mirna Džamonja and Duško Pavlović who initiated this event and have lightened up the spark within you and put in a lot of effort to organize this event. Sincere thanks to the Editorial board of the Sarajevo Journal of Mathematics, too, who with Mirna handled the event throughout. Finally, I would like to thank all the participants who took the time to attend and be with me at this event and thus contribute to making my jubilee very successful and unforgettable. Thanks again everyone. Mirjana Vuković